Impact of COVID-19 Outbreak on Oral Healthcare Services - T.O. Aladelusi (Nigerian Dental Association, 2020)
Objectives: To assess the impact of COVID-19 outbreak on patient attendance at the dental clinic, University College Hospital, Ibadan and to make recommendations on how the oral healthcare services can adapt and evolve practices to appropriately care for increasing patients' load following the ease of lockdown. Materials and Methods: The attendance records of patients in the second quarter of 2019 and 2020 was retrieved from the medical records department of the Dental clinic of the University College Hospital, Ibadan and reviewed. Data collected included age, gender and the specialty clinic attended. Descriptive statistics were used to analyse the data. Frequencies and mean age were calculated and comparison of attendance was done using the student t test. Results: Three thousand, six hundred and seventy patients were seen in the second quarter of 2019 while 1276 were attended to during the same period in 2020. This showed a 66% decrease in clinic attendance in the period under review with reduction of 86.99% and 26.28% in April and June of these years respectively. The reduction in the attendance in the second quarter of 2019 compared to the second quarter of 2020 was statistically significant (p=0.002). Conclusion: The COVID-19 epidemic is still a major public health concern that may still persist for some time therefore preventative measures are necessary to curtail the spread of this viral disease. Dental practitioners have an important role in this global fight for preventing the transmission of infectious diseases such as COVID-19 and must be trained ready for this role. It is recommended that pragmatic approaches including standard infection prevention and control measures must be strictly adhered to in the oral health care settings to mitigate the spread of infection.